Accessibility, Utilisation and Perceived Usefulness of Library Resources on the Study Habits of Undergraduates in Kwara State Universities - Bankole, Qudus Ajibola; Adelodun, Abdullateef Funsho; Sulaiman, Kabir Gambari; Saliu, Abdulfatai (Inkunabula: Journal of Library Science and Islamic Information, 2024)
The research explores the accessibility, utilisation, and perceived usefulness of library resources among undergraduates in Nigeria, aiming to enhance their study habits. Conducted through a survey with 410 undergraduates from three universities offering library and information science programs, data was collected via questionnaires and analysed descriptively and inferentially. Findings revealed predominant usage of library resources via the university library, departmental library, and electronic databases, including journals, OPAC, textbooks, databases and projects/theses. Students acknowledged the usefulness of these resources in research projects, knowledge acquisition, learning quality, and assignments. Common study habits encompassed post-lecture review, utilising breaks for study, minimizing distractions and prioritise academic commitments over social activities. Statistical analyses showcased significant correlations and indicated that independent variables collectively influenced 48.3% of observed variations in study habits. Ultimately, the study suggests that leveraging accessible, useful library resources could enhance undergraduates' study habits and foster academic success.